The role of host mobility in the transmission and spread of Echinococcus granulosus: A Chile-based mathematical modeling approach. - Richard Lagos; Juan Pablo Gutiérrez-Jara; Beatriz Cancino-Faure; Leidy Yissedt Lara-Díaz; Aníbal Coronel (PLoS Neglected Tropical Diseases)
This paper explores, as a proof-of-concept, the impact of definitive and intermediate host mobility on the transmission and spread of cystic echinococcosis by characterizing disease dynamics using three classical epidemic models: S-E-I-R for the accidental intermediate host, S-E-I for the habitual intermediate host, and S-I-S for the definitive host. The simulations revealed a significant relationship between the mobility of dogs and the increase in infected sheep. Specifically, for each infected dog, there were twice as many infected sheep as in a situation where mobility was not a factor. The initial conditions took into account that the prevalence of the disease in dogs is higher in rural areas than in peri-urban areas, as has been observed in the Magallanes region of Chile. The results of the simulations suggest that mobility can have a role in the propagation of the disease in humans. Furthermore, the sensitivity index on [Formula: see text] indicates that a 10% reduction in the average time spent by peri-urban dogs in urban and rural areas could result in a decrease of approximately 1% in [Formula: see text] In conclusion, including the host mobility factor allows us to observe that, in general, the number of infected in the domestic cycle of the disease increases, i.e., our mathematical model provides valuable information on the impact of host mobility on the transmission and spread of cystic echinococcosis.